2000
DOI: 10.1034/j.1600-0420.2000.078001093.x
|View full text |Cite
|
Sign up to set email alerts
|

Vogt‐Koyanagi‐Harada syndrome in a pregnant patient treated with high‐dose systemic corticosteroids

Abstract: ABSTRACT.Purpose: Vogt-Koyanagi-Harada (VKH) syndrome is usually treated with highdose systemic corticosteroids. However, in a pregnant patient with VKH syndrome, the effects of high-dose corticosteroids on the fetus are controversial. We discuss treating VKH syndrome during pregnancy, systemic corticosteroids, and abnormalities in the delivered infant. Methods: Case report and literature review. Results: A 26-year-old Japanese woman in the 16 th week of gestation was diagnosed with VKH syndrome and treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 9 publications
0
12
0
1
Order By: Relevance
“…There are no reported side effects in other similar case reports published by Doi et al [40] and Miyata et al [41].…”
Section: Maternal Risksmentioning
confidence: 84%
“…There are no reported side effects in other similar case reports published by Doi et al [40] and Miyata et al [41].…”
Section: Maternal Risksmentioning
confidence: 84%
“…In another report, Steahly detailed the adverse effects of high-dose corticosteroid treatment for VKH disease during pregnancy in two cases: one patient suffered a spontaneous abortion, and the other delivered a premature infant [ 5 ]. Doi et al also reported that a pregnant VKH patient treated with a high-dose systemic corticosteroid delivered a low-birth-weight infant with an epibulbar dermoid, lipodermoids, and preauricular appendages, although the relationship among VKH disease, systemic corticosteroids, spontaneous abortion, and congenital malformation was not clear [ 6 ]. Østensen and Skomsvoll stated that, administered during early pregnancy, corticosteroids are also considered a risk factor for the development of oral clefts [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a study, the use of systemic steroids in midtrimester did not cause any abnormalities in the baby 7. In another study, high-dose systemic steroids produced low birth weight in the baby 8. The other systemic effects noted in the baby were reported to be unconnected to the steroids.…”
Section: Discussionmentioning
confidence: 96%